The rat Toxo1 locus directs toxoplasmosis outcome and controls parasite proliferation and spreading by macrophage-dependent mechanisms - Cavaillès, Pierre (National Academy of Sciences, 2006)
Toxoplasmosis is a healthcare problem in pregnant women and immunocompromised patients. Like humans, rats usually develop a subclinical chronic infection. LEW rats exhibit total resistance to Toxoplasma gondii infection, which is expressed in a dominant mode. A genome-wide search carried out in a cohort of F(2) progeny of susceptible BN and resistant LEW rats led to identify on chromosome 10 a major locus of control, which we called Toxo1. Using reciprocal BN and LEW lines congenic for chromosome 10 genomic regions from the other strain, Toxo1 was found to govern the issue of T. gondii infection whatever the remaining genome. Analyzes of rats characterized by genomic recombination within Toxo1, reduced the interval down to a 1.7-cM region syntenic to human 17p13. In vitro studies showed that the Toxo1-mediated refractoriness to T. gondii infection is associated with the ability of the macrophage to impede the proliferation of the parasite within the parasitophorous vacuole. In contrast, proliferation was observed in fibroblasts whatever the genomic origin of Toxo1. Furthermore, ex vivo studies indicate that macrophage controls parasitic infection spreading by a Toxo1-mediated mechanism. This forward genetics approach should ultimately unravel a major pathway of innate resistance to toxoplasmosis and possibly to other apicomplexan parasitic diseases.